“Mysteries divulged”: Philemon Holland’s Paratexts and the Translation of Pliny’s Natural History in Early Modern England - Belle, Marie-Alice (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
This paper seeks to situate Philemon Holland’s 1601 translation of Pliny’s Natural History in the context of the development of early modern English science. While Holland’s Pliny has traditionally been studied in terms of the early modern reception of the Classics, the establishment of an English rhetoric of translation and the development of English prose, this paper focuses on the discursive and paratextual strategies at work in Holland’s rendering of the botanical and medical books of Pliny’s Natural History. Drawing on and broadening Genette’s definition of paratexts as liminary spaces of authorial—or translatorial—control and self-fashioning, the paper explores the complexities of Holland’s self-defined translation project as the “divulging” of Pliny’s medical and botanical knowledge to a broadened readership. Whereas the prefaces to both volumes of the Natural History rely on the rhetoric of utilitas, or usefulness, to span the spectrum of potential readers, from schoolchildren and “inferior readers” to Humanist scholars and physicians, a closer analysis of the marginal annotations in books XIX to XXVII of the Natural History shows Holland integrating the Continental tradition of learned commentary denouncing the factual, interpretive, and methodological errors in Pliny’s treatise. It is argued that the resulting tension between text and paratext, and between Holland’s prefaces and other kinds of liminary material, ultimately reflects changing attitudes towards ancient science, and the very nature of scientific knowledge in early modern England.